French Cultural Diplomacy Strategy through Social Media: Analysis of IFI Indonesia Instagram Content - Yulianti, Yumi; Made Panji Teguh Santoso (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2025)
This study analyses the cultural diplomacy strategies of France through the Instagram social media platform, as implemented by the Institut Français Indonesia (IFI). Using a descriptive qualitative approach and content analysis of six selected posts from March to May 2025, the study identifies the effectiveness of cultural content in building audience engagement. The results show that educational content, such as promotions for the LPDP–France scholarship, achieved the highest engagement rate (16.15%), followed by performing arts (3.23%) and film (1.57%). Meanwhile, culinary and interactive content, despite having lower engagement rates, play a crucial role in fostering interpersonal relationships (people-to-people diplomacy). Narrative analysis in captions and the use of Instagram Story features reveal adaptive communication strategies that combine persuasive copywriting techniques with contextual cultural approaches. In conclusion, IFI successfully leveraged Instagram as a tool for digital cultural diplomacy through visual content, emotional narratives, and participatory interactions, effectively strengthening France's soft power in Indonesia.